Human gestational N‐methyl‐d‐aspartate receptor autoantibodies impair neonatal murine brain function. Issue 5 (18th September 2019) - Jurek, Betty; Chayka, Mariya; Kreye, Jakob; Lang, Katharina; Kraus, Larissa; Fidzinski, Pawel; Kornau, Hans‐Christian; Dao, Le‐Minh; Wenke, Nina K.; Long, Melissa; Rivalan, Marion; Winter, York; et al.
Abstract : Objective: Maternal autoantibodies are a risk factor for impaired brain development in offspring. Antibodies (ABs) against the NR1 (GluN1) subunit of the N ‐methyl‐d ‐aspartate receptor (NMDAR) are among the most frequently diagnosed anti‐neuronal surface ABs, yet little is known about effects on fetal development during pregnancy. Methods: We established a murine model of in utero exposure to human recombinant NR1 and isotype‐matched nonreactive control ABs. Pregnant C57BL/6J mice were intraperitoneally injected on embryonic days 13 and 17 each with 240μg of human monoclonal ABs. Offspring were investigated for acute and chronic effects on NMDAR function, brain development, and behavior. Results: Transferred NR1 ABs enriched in the fetus and bound to synaptic structures in the fetal brain. Density of NMDAR was considerably reduced (up to −49.2%) and electrophysiological properties were altered, reflected by decreased amplitudes of spontaneous excitatory postsynaptic currents in young neonates (−34.4%). NR1 AB‐treated animals displayed increased early postnatal mortality (+27.2%), impaired neurodevelopmental reflexes, altered blood pH, and reduced bodyweight. During adolescence and adulthood, animals showed hyperactivity (+27.8% median activity over 14 days), lower anxiety, and impaired sensorimotor gating. NR1 ABs caused long‐lasting neuropathological effects also in aged mice (10 months), such as reduced volumes of cerebellum, midbrain, and brainstem. Interpretation: The data collectively support a model in which asymptomatic mothers can harbor low‐level pathogenic human NR1 ABs that are diaplacentally transferred, causing neurotoxic effects on neonatal development. Thus, AB‐mediated network changes may represent a potentially treatable neurodevelopmental congenital brain disorder contributing to lifelong neuropsychiatric morbidity in affected children. ANN NEUROL 2019;86:656–670